1991
DOI: 10.1017/s0016672300028962
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of the transposable elementUqin Iowa stiff stalk synthetic maize populations

Abstract: The Uq transposable element is one of two transposable elements consistently found in maize (Zea mays L.) populations. Populations developed from two independent recurrent selection programs initiated in the Iowa Stiff Stalk Synthetic (BSSS) maize population were tested for the frequency of Uq transposable elements to determine how Uq frequency has changed with cycles of recurrent selection. In the first programme, 13 cycles of half-sib and S 2 progeny recurrent selection [BSSS(S)C13] have been completed and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Both of the populations for which parameter estimates are available, BS13(S)C0 and BSCB1( R )C13, were selected for grain yield and grain moisture with a greater emphasis placed on grain yield. BS13(S)C0 was initially put through 7 cycles of half‐sib selection, and BSCB1( R )C13 has undergone 13 cycles of reciprocal improvement with the BSSS(R) population (Penny and Eberhart, 1971; Lamkey et al, 1991; Keeratinijakel and Lamkey, 1993; Schnicker and Lamkey, 1993; Holthaus and Lamkey, 1995). Given observed covariance parameter estimates for grain yield in these two popluations, it appears that selection has produced similar genotypic covariance structures in two populations that differ in their genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Both of the populations for which parameter estimates are available, BS13(S)C0 and BSCB1( R )C13, were selected for grain yield and grain moisture with a greater emphasis placed on grain yield. BS13(S)C0 was initially put through 7 cycles of half‐sib selection, and BSCB1( R )C13 has undergone 13 cycles of reciprocal improvement with the BSSS(R) population (Penny and Eberhart, 1971; Lamkey et al, 1991; Keeratinijakel and Lamkey, 1993; Schnicker and Lamkey, 1993; Holthaus and Lamkey, 1995). Given observed covariance parameter estimates for grain yield in these two popluations, it appears that selection has produced similar genotypic covariance structures in two populations that differ in their genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Within 63 four years, however, more than 90% of maize grown in Iowa had transitioned to higher-yielding 64 hybrids created by controlled crosses, and the rest of the Corn Belt soon followed (Reif et al 65 2005). The transition to single-cross hybrids was largely driven by key founder lines (B14, B37, 66 and B73) derived from a pivotal maize population called Iowa Stiff Stalk Synthetic (BSSS), 67 which was created in the 1930s by intermating 16 inbred lines (Lamkey et al 1991;Reif et al 68 2005). These founder lines and their combinations, referred to as Stiff Stalk lines, became 69 preferentially used as females in hybrid breeding schemes, while other inbred lines that 70 combined well with them were used as males (Reif et al 2005).…”
Section: Introduction 29mentioning
confidence: 99%
“…Exemplifying this importance, in 1980, 19% of all parental materials of hybrids in the United States were inbred lines extracted from a single population, the Iowa Stiff Stalk Synthetic (BSSS), one of the most frequently used germplasms in the world (LAMKEY et al, 1991). In a more recent plan, Mikel (2011) studied the genetic compositions of more than 300 inbreds with registered pedigrees in the United States between 2004 and 2008 and from various private breeding programs from the US and concluded that just two germoplasms, the BSSS and Iodent, together contributed with more than two-thirds of the genes in these inbred lines.…”
Section: Introductionmentioning
confidence: 99%